2022
DOI: 10.3389/fonc.2022.920316
|View full text |Cite
|
Sign up to set email alerts
|

Redox Mechanisms in Cisplatin Resistance of Cancer Cells: The Twofold Role of Gamma-Glutamyltransferase 1 (GGT1)

Abstract: Cisplatin (CDDP) is currently employed for the treatment of several solid tumors, but cellular heterogeneity and the onset of drug resistance dictate that suitable biomarkers of CDDP sensitivity are established. Studies on triple-negative breast cancer (TNBC) have recently confirmed the involvement of gamma-glutamyltransferase 1 (GGT1), whose enzyme activity expressed at the cell surface favors the cellular resupply of antioxidant glutathione (GSH) thus offering cancer cells protection against the prooxidant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Decreased levels of reduced GSH and enzymes involved in GSH synthesis were identified to play a key role in cisplatin resistance [157]. Pompella et al showed that the enzyme gamma-glutamyltransferase 1 (GGT1) expression on the surface of the cell favors the cellular resupply of antioxidant glutathione (GSH) which in turn favors protection against cisplatin by the formation of glycyl-cysteine dipeptide which forms an adduct with cisplatin thereby preventing its entry into the cell and its interaction with the DNA [158,159]. Platinum-resistant ovarian cancer cells showed increased dependency on glutamine metabolism as ASCT2 and GA were significantly upregulated.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…Decreased levels of reduced GSH and enzymes involved in GSH synthesis were identified to play a key role in cisplatin resistance [157]. Pompella et al showed that the enzyme gamma-glutamyltransferase 1 (GGT1) expression on the surface of the cell favors the cellular resupply of antioxidant glutathione (GSH) which in turn favors protection against cisplatin by the formation of glycyl-cysteine dipeptide which forms an adduct with cisplatin thereby preventing its entry into the cell and its interaction with the DNA [158,159]. Platinum-resistant ovarian cancer cells showed increased dependency on glutamine metabolism as ASCT2 and GA were significantly upregulated.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…Mutations in Slc7a11, Ggt1, Mfsd12, Clcn7, Ostm1, Sox10, and several as yet undefined genes have all been shown to reduce pheomelanin pigmentation in mouse with no or modest impact on eumelanin production [10,[66][67][68][69][70][71][72]. Several of these genes (Slc7a11, Mfsd12, and Ggt1) impact cysteine uptake, intracellular transport, or incorporation into glutathione [10,73,74], and thus might share a mechanistic basis with Comtd1 for their impact on pheomelanin synthesis. Clcn7 and Ostm1 encode the subunits of the CLC7 chloride transporter that impacts lysosomal pH [75], and thus might alter the pH of melanosomes promoting specifically pheomelanin synthesis.…”
Section: Plos Geneticsmentioning
confidence: 99%